RETRACTION NOTICE "Planting depth management increases early growth, aboveground biomass, and carbon storage of Eucalyptus pellita at Ultisols in South Sumatra" - Pandu Yudha Adi Putra Wirabuana; Ronggo Sadono; Sergian Juniarso (Journal of Degraded and Mining Lands Management, 2020)
This article entitled “Planting depth management increases early growth, aboveground biomass, and carbon storage of Eucalyptus pellita at Ultisols in South Sumatra” (2020), authored by Pandu Yudha Adi Putra Wirabuana, Ronggo Sadono, Sergian Juniarso, published in Volume 7, Issue 4. of Journal of Degraded and Mining Lands Management, pp. 2253-2261 has been retracted as requested by the authors.